Michael Oakeshott : notebooks, 1922-86 - O'Sullivan, Luke (Michael Oakeshott Selected Writings., 2014)
A collection of 6 volumes of Oakeshott''s work: Notebooks, 1922-86, Early Political Writings 1925-30, The Concept of a Philosophical Jurisprudence, Vocabulary of a Modern European State, Lectures in the History of Political Thought, and What is History?